Red blood cell-derived semaphorin 7A promotes thrombo-inflammation in myocardial ischemia-reperfusion injury through platelet GPIb - Köhler, David; Granja, Tiago; Volz, Julia; Koeppen, Michael; Langer, Harald F.; Hansmann, Georg; Legchenko, Ekaterina; Geisler, Tobias; Bakchoul, Tamam; Eggstein, Claudia; Häberle, Helene A.; Nieswandt, Bernhard; et al. (Nature communications, 2020)
Myocardial ischemia is one of the leading health problems worldwide. Therapy consists of the restitution of coronary perfusion which is followed by myocardial inflammation. Platelet–neutrophil interaction is a crucial process during inflammation, yet its consequences are not fully understood. Here, we show that platelet–neutrophil complexes (PNCs) are increased in patients with acute myocardial infarction and that this is associated with increased levels of neuronal guidance protein semaphorin 7A (SEMA7A). To investigate this further, we injected WT animals with Sema7a and found increased infarct size with increased numbers of PNCs. Experiments in genetically modified animals identify Sema7a on red blood cells to be crucial for this condition. Further studies revealed that Sema7a interacts with the platelet receptor glycoprotein Ib (GPIb). Treatment with anti-Sema7a antibody protected from myocardial tissue injury. In summary, we show that Sema7a binds to platelet GPIb and enhances platelet thrombo-inflammatory activity, aggravating post-ischemic myocardial tissue injury. Reperfusion injury following myocardial ischemia is aggravated by inflammation and platelet–neutrophil complex formation. Here the authors show that semaphorin 7A binds to platelet GPIb, enhancing platelet–neutrophil interaction and increasing post-ischemic myocardial tissue injury, and that blockage of semaphorin 7A is protective.